Global Encyclopedia of Public Administration, Public Policy, and Governance 2020
DOI: 10.1007/978-3-319-31816-5_4039-2
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Ihsan Behavior

Abstract: Organizational Ihsan behavior, as the current entry defines it, is a virtue-based discretionary behavior enhancing the welfare of organization and its members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Organizations strive to preserve stakeholders' well-being and long-term survival, particularly during uncertain times – an example is private insurance companies in Syrian Arab Republic (Hazzi, 2020), where the armed conflict is still raged since 2011. In a different setting, firsthand observation has shown that some international corporations fail to pursue sustainability (Hazzi and Aldejwi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Organizations strive to preserve stakeholders' well-being and long-term survival, particularly during uncertain times – an example is private insurance companies in Syrian Arab Republic (Hazzi, 2020), where the armed conflict is still raged since 2011. In a different setting, firsthand observation has shown that some international corporations fail to pursue sustainability (Hazzi and Aldejwi, 2021).…”
Section: Introductionmentioning
confidence: 99%